Current status and future prospects of renewable energy: A case study. Issue 21 (1st November 2020) - Balakrishnan, P.; S. Shabbir, M.; F. Siddiqi, A.; Wang, X.
ABSTRACT: The aim of this study was to analyze renewable energy installed capacity of developing countries by focusing on China as the leading country in renewable energy development to determine the reasons for growth or suspension of developments. Then, recent laws and policies of renewable energy systems were discussed in developing countries, to analyze their policies toward the use of renewable electricity. According to the findings, the most important barrier to further renewable energy developments in such countries is the unwillingness of the private sector to make investments due to considerable expenditures and the late return of capital. It was suggested in this study that governmental supports and the guaranteed purchase of generated electricity could resolve the problems to some extent.